Attracting investment for Africa's protected areas by creating enabling environments for collaborative management partnerships. (March 2021) - Lindsey, P.; Baghai, M.; Bigurube, G.; Cunliffe, S.; Dickman, A.; Fitzgerald, K.; Flyman, M.; Gandiwa, P.; Kumchedwa, B.; Madope, A.; Morjan, M.; Parker, A.; et al.
Abstract: Africa's Protected Area (PA) estate includes some of the world's most iconic wildlife and wildlands and preserves ecosystem services upon which people depend. However, Africa's PAs are facing a growing array of threats resulting in significant degradation, factors compounded by chronic funding shortages. In this opinion piece, drawing from the available literature and collective experience of the author group, we look at the potential for collaborative management partnerships (CMPs) between state wildlife agencies and Non-Governmental Organisations (NGOs) to attract investment and technical capacity to improve PA performance. The three main CMP models—financial and technical support, co-management, and delegated management—yield median funding that is 1.5, 2.6 and 14.6 times greater than baseline state budgets for PA management. However, several factors limit the scaling of CMPs in Africa. Significant barriers include concerns from African governments, such as reluctance to engage in co-management and delegated CMPs due to perceptions that such partnerships may represent an admission of failure, result in a loss of revenues for government, or undermine sovereignty. There are also constraints associated with NGOs and donors that limit scaling of CMPs. We discuss how these issues might be addressed and propose a reframing of the discourse around CMPs. Specifically, we recommend that governments view CMPs as strategic, proactive tools that will enable them to unlock funding, investment and expertise for conservation and make recommendations to attract such investment. Preliminary evidence and the experience of the author group suggests that expanding CMPs for PAs could; improve PA management; share the costs of protecting Africa's PAs with the global community; build local capacity; help protect the ecosystem services upon which Africa's economies depend; stimulate rural development; and benefit local communities.